Manajemen Pendidikan Keluarga dalam Meningkatkan Hasil Belajar Peserta Didik di MI Al Mukarromah Kebumen - Silmi Muhimatul Chasanah; Dian Fitria Anwar; Fadal Sa’dallah Achmad; Ghoniyatun Choeriah; Siti Fatimah; Bahrun Ali Murtopo (LPPM IAINU Kebumen, 2022)
Family is the first and foremost educational institution for a child. Alliances between families and schools, especially in education, can improve children's learning achievements because when parents and schools collaborate well with each other, children can also behave and show better performance at school. The purpose of this study is to analyze family education management in improving student learning outcomes at MI Al Mukarromah Kebumen. This research is a classroom action research that was carried out for 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were school principals, third grade students at MI Al Mukarromah Kebumen, and student guardians (parents). Data collection techniques using interviews and documentation. The results of the analysis show that parents' efforts to improve student learning outcomes are by always taking the time to accompany their children while studying at home and always supervising their children while at home or outside the home. there are several supporting factors and inhibiting factors of learning outcomes from parents. The supporting factors are parental attention, parenting, and facilitating learning facilities and infrastructure, while the inhibiting factors are parents' busyness and mastery of material. So it can be concluded that there is an increase in student learning outcomes if parents always have time to accompany their children in learning, and children become more enthusiastic if their parents always pay attention to their children.